Amazement and Trepidation: Implications of AI-Based Natural Language Production for the Teaching of Writing - Anson, Chris M.; Straume, Ingerid (Journal of Academic Writing, 2022)
AI-based natural language production systems are currently able to produce unique text with minimal human intervention. Because such systems are improving at a very fast pace, teachers who expect students to produce their own writing—engaging in the complex processes of generating and organizing ideas, researching topics, drafting coherent prose, and using feedback to make principled revisions that both improve the quality of the text and help them to develop as writers—will confront the prospect that students can use the systems to produce human-looking text without engaging in these processes. In this article, we first describe the nature and capabilities of AI-based natural language production systems such as GPT-3, then offer some suggestions for how instructors might meet the challenges of the increasing improvement of the systems and their availability to students.